Corrigendum to “A novel photocatalyst of Y2O3-BaO-ZnO ternary system for enhanced photocatalytic degradation of carbofuran insecticide” [Mater. Today Commun. 40 (2024) 109501] (Materials Today Communications (2024) 40, (S235249282401482X), (10.1016/j.mtcomm.2024.109501)) - Sujinnapram, Supphadate; Krobthong, Sucheewan; Moungsrijun, Sasimonton; Boonruang, Chatdanai; Kaewtrakulchai, Napat; Eiad-Ua, Apiluck; Manatura, Kanit; Wongrerkdee, Sutthipoj (My University, 2024)
The authors regret that before the online release of our article, some information remained unnoticed during the proof correction. After careful consideration, we decided to make this corrigendum for our article. Typographical errors in Table 2: The correct unit of initial CBF concentration for the YBZ5 photocatalyst in Table 2 should be mg/L. The authors would like to apologise for any inconvenience caused.